Comparison of serum malondialdehyde levels determined by two different methods in patients with COPD: HPLC or TBARS method - Tug, T; Karatas, F; Terzi, SM; Ozdemir, N (Oxford Univ Press, 2005)
[Abstract Not Available]
Keywords: Obstructive Pulmonary-Disease; Acid; Plasma; Complexes; Assay